Забезпечення науковими кадрами електротехнічного комплексу України (1950–1960 рр.) - Тверитникова, Олена Євгенівна (Запорізький національний університет, 2014)
Розглянуто етапи формування системи підготовки і атестації наукових та науково-педагогічних кадрів електротехнічного профілю в провідних вищих технічних навчальних закладах та академічних установах України впродовж 1950–1960 рр. На основі аналізу нормативно-правових документів встановлено характерні ознаки функціонування інституту аспірантури та докторантури на тлі освітньої державної політики другої половини ХХ ст. Висвітлено особливості підготовки наукових кадрів для електротехнічного комплексу, зокрема досліджено діяльність спеціалізованих вчених рад, виокремлено здобутки та вказано на недоліки у розвитку системи формування наукового та освітнього потенціалу того часу.

It is dealt with formation stages of a training and certification system of scientific and pedagogical personnel with electrotechnical specialization in leading technical colleges and academic institutions of Ukraine during 1950–1980 years. Based on analyze of legal documents it’s determined the main features of functioning of postgraduate and doctoral institution against the background of educational public policy of the second half of XX century. It is outlined the features of a preparation of scientific personnel for electrotechnical complex, in particular it is investigated the operations of academic councils; it is singled out the weaknesses and achievements during different periods of development of the formation system of a scientific and educational potential.
Scientific personnel support of electrotechnical system of Ukraine (1950–1980)
Keywords: вища електротехнічна школа України; аспірантура; докторантура; спеціалізована вчена рада; high electrotechnical school of Ukraine; formation of scientific personnel; postgraduate; doctoral institution; specialized academic council